SURGICAL TREATMENT OF PATIENTS WITH MULTIPLE INTRACRANIAL ANEURYSMS AND ACUTE SEVERE SUBARACHNOID HEMORRHAGE - D.V. LITVINENKO; E.I. ZYABLOVA; V.V. TKACHYOV; G.G. MUZLAEV (Паёми Сино, 2022)
About 40% of patients with multiple intracranial aneurysms (MIAs) are admitted with poor-grade subarachnoid haemorrhage (Hunt & Hess Grades IVV). Therefore, an approach to identify the most appropriate strategy for an individual patient should be applied to obtain the best functional outcomes. However, there is still no consensus on selecting proper MIAs treatment in patients with acute subarachnoid haemorrhage with localization of all aneurysms in the surgical intervention area. The article presents a case of a 43-year-old patient with MIAs: a ruptured aneurysm of the anterior communicating artery (ACA) and intact right pericallosal and right middle cerebral arteries (MCA). The first stage included clipping the ruptured ACA aneurysm and decompressive craniectomy. After stabilization of the patient's condition, the second stage of treatment was performed: clipping the aneurysms of the right pericallosal and right MCA and autologous cranioplasty. The patient was discharged from the hospital in satisfactory condition. The presented case demonstrates the need for a flexible individual approach to treating patients with MIAs and acute subarachnoid bleeding. Staged surgical treatment and performing as the second stage clipping of intact aneurysms with simultaneous early cranioplasty after compensating the patient's condition allowed for good treatment outcomes.